Programa da nota fiscal eletrônica em Goiás: elaboração de plano de ação para melhorias na política pública - Vieira, Patrícia Araújo (2016)
Innovation in the public sector, and in particular technological innovation, is an example of change within public organizations. One form of technological innovation is e-government, which is defined as the modernization of public administration through the usage of information and communication technologies (ICTs). Examples that stands out of the e-government programs include the ones developed by the tax administration, such as the Electronic Invoice (NF-e). Although it is an important program and used throughout Brazil, there is still little study about it and there is no evaluation of the performance of this type of public fiscal policy in the country’s Treasury Departments. The aim of this study was to evaluate, according to the parameters of effectiveness and effectiveness itself, the Electronic Invoice program in the State of Goiás, using the guidelines of the GESPÚBLICA guide for evaluating public policies. Specifically, it was intended to make a diagnosis to identify the main problems with NF-e in the State, to propose solutions and implement those that were feasible during the execution of this research. In order to measure the effectiveness, a SEFAZ database was used to analyze the sharing of tax documents. Furthermore, to measure the effectiveness, a questionnaire was applied to the fiscal auditors of the State’s Department of Finance about the changes in the inspection after the implantation of NF-e. Through the evaluation of public policy, it was identified that in relation to effectiveness, the NF-e program in Goiás does not match the goals proposed for synchronization of fiscal documents. It was also found that the tax of sending the fiscal documents to the National Environment does not reach all the authorized documents and the period of time to send and to receive the fiscal documents is very long. Regarding effectiveness, the conclusion is that that the NF-e program has brought improvements to the inspection and audit processes to the State’s Department of Finance. The main improvement was the speed of the audits, due to the increase of the facility and the velocity in obtaining the data for inspection. It is also worth mentioning the real-time monitoring of the operations, which reduces the response time of audits in relation to possible fraud and evasion. Regarding the work intervention, changes were made in the synchronism system of fiscal documents, according to the solution proposed from the diagnosis made and as a result a significant improvement in the timing of the fiscal documents to the National Environment was obtained.